KAJIAN PENGGUNAAN RAGI TAPE TERHADAP HASIL UJI ORGANOLEPTIK DAN KEKERASAN DURI DAGING PINDANG IKAN BANDENG (Chanos chanos) Study of the Use of Yeast Tape on Organoleptic and Hardness Test Results for Pindang Meat Fish Milkfish (Chanos chanos) - Ida Ratnasari; Maryani Maryani (Agrienvi: Jurnal Ilmu Pertanian, 2018)
This study aims to determine the effect of yeast tape on hardness of pindang bandeng (Chanos chanos) thorns, while the benefits are expected to contribute ideas in fish processing business for milkfish with soft thorns using yeast tape in an easy, inexpensive way , and can be done by everyone, and can produce soft textured quality by not damaging the nutritional content of pindang bandeng fish. The results of this study indicate that from the results of chemical tests on milkfish pindang using different concentrations of yeast tape did not have a significant effect on protein content, water content and TPC test, while the organoleptic test significantly affected taste, texture, bone and color.